A Direct Detection Fiber Optic Distributed Acoustic Sensor With a Mean SNR of 7.3 dB at 102.7 km - Faruk Uyar; Talha Onat; Canberk Unal; Tolga Kartaloglu; Ekmel Ozbay; Ibrahim Ozdur (IEEE Photonics Journal)
In this work, we present the experimental results of a direct detection $φ $ -OTDR based distributed acoustic sensor system. The system uses two cascaded acousto-optic modulators in order to generate optical pulses with very high extinction ratio and dual photodetector scheme for high dynamic range. The proposed schemes are investigated in detail and their performance enhancement is experimentally verified. Four piezoelectric based fiber stretchers are placed on a ∼104 km single-mode test fiber at the distances of 1 km, 10 km, 87 km and 102.7 km and used for perturbation tests. The stretchers generated vibration signals which are analyzed to quantify the system performance. The signal-to-noise ratio (SNR) of vibration signals at the monitored distances is measured over the 12-hour recorded data within 34-second time windows considering the multi-point random interference of scattered light and fading phenomena. Using the 12-hour data, SNR histograms at four different locations are generated and mean SNR values are obtained. The signals received from 102.7 km has a maximum SNR of 24.7 dB and a mean SNR of 7.3 dB with a spatial resolution of 15 m. To the best of our knowledge, this is the highest-range reported direct detection $φ $ -OTDR based distributed acoustic sensor system.